Dementia in Parkinson’s disease - Hu, M; Baig, F (Oxford University Press, 2020)
Lewy body dementia includes Parkinson’s disease dementia (PDD) and dementia with Lewy bodies (DLB), and is the second most common form of dementia after Alzheimer’s disease (AD). Both conditions share significant phenotypic and pathological signatures but differ in terms of whether Parkinsonian symptoms appear first (PDD) or after/the same time as cognitive symptoms (DLB). In the United Kingdom, over 100,000 people are affected, with numbers predicted to double by 2050. Average care costs per patient are more than double those of AD, reflecting the associated multi-morbidity and unmet therapeutic needs. PDD has a long-term cumulative prevalence of 80% and major consequences for independence, nursing home admission, psychiatric comorbidity, caregiver burden, and mortality. Consequently, there is interest in a potential transition stage—Parkinson’s disease with mild cognitive impairment (PD-MCI)—to identify those at increased risk for PDD, to facilitate intervention studies. Advances in both symptomatic and disease-modifying treatments have so far been limited. Future research must address patient-specific factors influencing variability in treatment response and progression to be effective.